Quantifying Temporomandibular Joint Synovitis in Children With Juvenile Idiopathic Arthritis - Resnick, Cory M.; Vakilian, Pouya M.; Breen, Micheál; Zurakowski, David; Caruso, Paul; Henderson, Lauren; Nigrovic, Peter A.; Kaban, Leonard B.; Peacock, Zachary S. (Arthritis care & research (2010), 2016)
Objective Juvenile idiopathic arthritis (JIA) frequently affects the temporomandibular joints (TMJs) and is often undetected by history, examination, and plain imaging. Qualitative assessment of gadolinium‐enhanced magnetic resonance images (MRIs) is currently the standard for diagnosis of TMJ synovitis associated with JIA. The purpose of this study is to apply a quantitative analysis of synovial enhancement to MRIs of patients with and without JIA to establish a disease threshold and sensitivity and specificity for the technique. Methods This is a retrospective case–control study of children (age ≤16 years) who had MRIs with gadolinium including the TMJs. Subjects were divided into a JIA group and a control group. From a coronal T1‐weighted image, a ratio (enhancement ratio [ER]) of the average pixel intensity within three 0.2‐mm2 regions of interest (ROIs) in the TMJ synovium to that of a 50‐mm2 ROI of the longus capitis muscle was calculated. Receiver operating characteristic curves were used to determine the sensitivity and specificity. The inter‐ and intraexaminer reliability was evaluated with Bland‐Altman plots and 2‐way mixed, absolute agreement intraclass correlation coefficients. Results There were 187 and 142 TMJs included in the JIA and control groups, respectively. An ER threshold of 1.55 had a sensitivity and specificity for detecting synovitis of 91% and 96%, respectively. The inter‐ and intraexaminer reliability was excellent. Conclusion Calculating a ratio of pixel intensity between the TMJ synovium and the longus capitis muscle is a reliable way to quantify synovial enhancement. An ER of 1.55 differentiates normal TMJs from those affected by inflammatory arthritis.